(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Putri RD, Dikson, Victor H, Sanjaya A, Pinontoan R. 2025. 16S rRNA metagenomic analysis of the Asiatic worker honeybee (Apis cerana) gut microbiome from an apiary in Bandung, Indonesia. Biodiversitas 26: 1666-1674. Honeybees play a crucial role in crop pollination, and consequently, in maintaining global food security. Therefore, understanding their survivability and resilience to natural and human-induced factors is crucial. One critical aspect is the gut microbiome of the honeybees, which is comprised of diverse endosymbiotic bacteria that enhance nutrient uptake and pathogen resistance. Asiatic honeybees (Apis cerana) are commonly managed in Indonesian apiaries for honey production. Therefore, this study aimed to investigate the gut microbiome of A. cerana from a Bandung apiary using 16S rRNA metagenomic sequencing and analytical tools, such as Kraken2, Bracken, SILVA 16S database, and Vegan R library for genus-level identification and Alpha Diversity analysis. The analysis identified 81 genera, including the dominant genera (97.9%) Gilliamella, Lactobacillus, Snodgrassella, Apibacter, and Bifidobacterium. Given that Gilliamella constituted more than 50% of the microbiome, the gut microbiome had high genus richness, but potentially low genus diversity, as indicated by the five Alpha Diversity indices Chao1, ACE, Simpson, Inverse Simpson and Shannon indices. The core genera revealed in this study are consistent with A. cerana samples from Korea and Japan, with Apibacter uniquely present in A. cerana but absent in Western A. mellifera. This study provides insights into the diversity of A. cerana gut microbiome from an apiary in Bandung, Indonesia.